Language and Deviation in Modern Communication Perspective - Heryono, Heri (International Journal of Psychosocial Rehabilitation, 2020)
Modern communication media has remarkably formed perspectives of modern people, especially their language. The world has recently embraced enormous multimedia communication network age to be meant as a set of sharable messages ubiquitously. It leads to service enhancing trend which turns users – in this term are modernage people–who suffer from great amount of information through various communication media. By simplifying the information acceptance, people receive consequences of novelty characteristics. It involves norms and behaviors which formerly regulated them; and by this consequences, deviations slightly emerged along with their dependency of communication media. The deviations generated from the modern communication media have various model; includes culture, language and social behavior. Those deviations scopes are mental deviation, which leads to verbal behavior caused by the inserting slang words (swear words) as popular language used in modern communication media; as it could be seen on television, cinema, social media and many other communication media which especially has an integration to internet. The second scope is symbolic deviation which covers emotion, sentiment and motivation of purposing criminal activities. This research methodology focused on observing behavior of people (users) who consciously felt some changes on themselves during they activity in modern communication media. Based on the research and observation to 30 participants who regularly access communication media through their gadgets, the language deviations were commonly found in several forms. First, they experienced situational deviation which leads to rebel, adolescent revolt and communicative matter. Second, the negative deviation which includes primary or temporary behavior deviation and secondary deviation which later becomes daily bad behavior.